Kesehatan Perusahaan Tourism di Masa Pandemi Covid19 dengan Metode K Means Clustering - Roosdiana Roosdiana; Maya Syafriana Effendi (Sosio e-Kons, 2021)
This research is aimed at seeing whether tourism companies listed on the Indonesia Stock Exchange during the Covid-19 pandemic are still classified as healthy or not. Measurement of the company's health level is carried out using the K-Means Algorithm. The results of the financial performance evaluation are grouped using the K-Means Algorithm. This algorithm will determine groups of tourism companies that are performing well (healthy) and companies that are not performing well (unhealthy) by determining groups based on the closest data distance to the centroid. From the results of the analysis of 32 tourism companies on the Indonesia Stock Exchange, data shows that there are 2 unhealthy tourism companies, namely Indonesia Pure Mas Company (MAMI) and PT. Sarimelati Kencar (PZZA) and 30 other tourism companies are in good health. Thus improvement and development steps are required for these 2 tourism companies.